Sustainability of Early Intensive Behavioral Intervention for Children With Autism Spectrum Disorder in a Community Setting. Issue 1 (January 2020) - Waters, Chanti F.; Amerine Dickens, Mila; Thurston, Sally W.; Lu, Xiang; Smith, Tristram
This study examined whether outcomes in early intensive behavioral intervention (EIBI) during a university-led multisite project could be replicated by the same community agency independently of the project. Participants, age 18 to 75 months at onset of intervention, were 48 children with autism spectrum disorder (ASD) enrolled in 35 hr per week of publicly funded, community-based EIBI for 3 years and 46 children who were matched on baseline characteristics and received early childhood services as usual (SAU) through local early childhood special education providers. Linear mixed models indicated that EIBI participants improved significantly more than SAU participants on standardized tests of IQ, nonverbal IQ, adaptive behavior, and academic achievement, administered by independent evaluators. Although limited by the use of a matched comparison group rather than random assignment, the study provides evidence for the sustainability of effective EIBI in community settings for children with ASD who start intervention at varying ages throughout early childhood.